Diagonal Export Controls to Counter Diagonal Transnational Attacks on Civil Society. (10th September 2020) - Lin, Herbert; Trachtman, Joel
Abstract: Modern geopolitics includes measures short of armed conflict designed to control decision-making in, and action by, target states. One increasingly significant category of these measures involves attacks by foreign states against civil society institutions in target states. Liberal states that seek to protect their civil societies from this interference seek to bolster civil society defences, to determine the origin of and respond to attacks and to deny relevant tools to potential attackers. With the rise of cyberspace, target states using purely territorial measures are increasingly impotent to protect their civil societies from foreign governmental hacking. Denying access to advanced hacking software by antagonist foreign states may assist in protecting target state civil societies. This article explores the possibility of denying hacking tools to potential attackers, identifies some of the problems and proposes a refinement of export controls that will permit greater protection with less disruption of desirable software development.